Age of mass maturing and commercial measure of the Gizhiga-Kamchatka herring in conditions of the active fishery renewal - Andrey A. Smirnov; Victor V. Ovchinnikov; Julia A. Elatintseva (Известия ТИНРО, 2016)
Data on age of mass maturing and biomass culmination for pacific herring from the Gizhiga-Kamchatka population in conditions of active fishery are presented. Dynamics of its age structure is considered for the periods before active fishery and after its renewal. After the fishery renewal, the portions of mature fish by age groups had increased and the age of mass maturing had decreased, the body length of mass maturing became smaller, the mean body length and weight had decreased for the majority of age groups, and the rate of maturing had increased for females. The established commercial measure corresponds well to recent biological structure of the population. There is concluded that the active fishery during five years has no negative impact on the state of the Gizhiga-Kamchatka population of herring.